Membangun Agribisnis Hortikultura Terintegrasi dengan Basis Kawasan Pasar - Bambang Irawan (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2003)
EnglishIn general, horticultural agribusiness particularly vegetables area characterized by four major conditions : (1) farmer produces the products for market orientation, (2) producer regions are concentrated in certain districts or sub-districts, (3) high fluctuation of product prices result from desynchronized of supply among producer regions, and (4) structure of agribusiness is dispersal, in other word, low institutional relationship among components of agribusiness. Under such conditions, development of horticultural agribusiness should be carried out by implementation of system approach in order to increase competitiveness of horticultural agribusiness. In this context two efforts required are : (1) promoting vertically integrated agribusiness through the development of partnership business among input traders-farmers-output traders, and (2) promoting regionally integrated production of producer districts having the same target of consumer regions. The two efforts are important to reduce fluctuation of products prices and to increase efficiency of resources allocation of each producer regions. In this relation, stakeholders groups functioned as supply regulator accros producer regions should be developed. IndonesianSecara umum, agribisnis hortikultura khususnya sayur-sayuran dicirikan oleh empat kondisi: (1) petani memproduksi untuk orientasi pasar; (2) wilayah produksi terkonsentrasi pada kabupaten-kabupaten atau kecamatan-kecamatan tertentu; (3) fluktuasi harga produksi yang tinggi disebabkan ketidaksinkronan suplay antar wilayah produksi; dan (4) struktur agribisnis yang tersekat-sekat, yang tampak dari hubungan kelembagaan yang lemah antar komponen agribisnisnya. Dalam kondisi demikian, pengembangan agribisnis hortikultura harus dilakukan dengan mengimplementasikan suatu pendekatan sistem sebagai upaya untuk meningkatkan daya saingnya. Dalam konteks ini dibutuhkan dua hal : (1) meningkatkan integrasi vertikal agribisnis melalui pengembangan kemitraan bisnis antara pedagang input-petani-pedagang output, serta (2) meningkatkan integrasi secara regional antar produsen pada wilayah-wilayah yang memiliki tujuan pasar yang sama. Kedua usaha tersebut berguna untuk mengurangi fluktuasi harga produk dan untuk meningkatkan efisiensi alokasi sumberdaya dari masing-masing wilayah sentra produksi. Dalam kaitan ini, perlu dikembangkan peranan kelompok-kelompok kepentingan (stakeholders) sebagai pengendali suplay antar wilayah sentra produksi.